Aspectos teóricos da análise da estrutura narrativa e a sua contribuição para a organização da informação - Cândido, Gilberto Gomes [UNESP]; Lima, Larissa de Melo [UNESP]; Moraes, João Batista Ernesto de [UNESP] (My University, 2013)
The theoretical aspects of the narrative structure of documents are discussed, using the Generative Trajectory of Meaning theory. In particular, the difficulties in identifying the subject of the documents (aboutness) are addressed from the linguistic and discursive semantics of Propp, Greimas Saussure, to show how these theories can improve the information representation processes.

Se discuten los aspectos teóricos de la estructura narrativa de los documentos, utilizando la teoría del Recorrido Generativo de Sentido. En particular, se abordan las dificultades en la identificación del tema de los documentos (aboutness) a partir de la lingüística y la semántica discursiva de Propp, Saussure y Greimas, para mostrar cómo estos fundamentos poden mejorar los procesos de representación documental.
Theoretical aspects of the structural narrative analysis and the contribution to the information organization
Aspectos teóricos del análisis de la estructura narrativa y su contribución a la organización del conocimiento